Black in Quebec : Part 1 - Black Community Resource Centre (BCRC) (2016)

BCRC Newsletter - Black Community Resource Centre (BCRC) (2005)

BCRC Newsletter - Black Community Resource Centre (BCRC) (2005)

BCRC Newsletter - Black Community Resource Centre (BCRC) (2006)

It is OK to Speak Up : Know Your Rights in the Workplace - Black Community Resource Centre (BCRC)

Your Rights at the Workplace - Black Community Resource Centre (BCRC)

The Education to Employability Study - Black Community Resource Centre (BCRC); Provincial Employment Roundtable of Quebec (2022)
In Québec, both the Black community and the English-speaking community occupy relatively precarious economic and employment positions: both experience higher-thanaverage unemployment rates and earn lower median after-tax incomes compared to the province’s total population. The English-speaking Black Community (ESBC) sits at the intersection of these two communities, and experiences the double marginalization of being both a racial and linguistic minority in Québec.

L'étude éducation à l'emplois (E2E) - Black Community Resource Centre (BCRC); Provincial Employment Roundtable of Quebec (2022)
Au Québec, la communauté noire et la communauté d'expression anglaise occupent toutes deux des positions relativement précaires sur le plan économique et de l'emploi : toutes deux connaissent des taux de chômage supérieurs à la moyenne et gagnent des revenus médians après impôt inférieurs à ceux de la population totale de la province. La communauté noire d'expression anglaise (CNEA) se trouve à l'intersection de ces deux communautés et subit la double marginalisation d'être à la fois une minorité raciale et linguistique au Québec.